Reconstructing Marital Readiness among Generation Z: Islamic Legal Responses to the 'Marriage is Scary' Phenomenon in Pamekasan - Yulia Anjani; Jamiliya Susantin; Urwatul Wusqo; Mujiburrohman (Jurnal Syariah dan Hukum Komparatif, 2026)
The 'marriage is scary' phenomenon has become increasingly prevalent among Generation Z and has significantly influenced how they perceive marriage as an institution characterized by risk and uncertainty. This study aims to analyze the factors contributing to the emergence of the 'marriage is scary' phenomenon among Generation Z in Pamekasan Regency and to reconstruct the concept of marital readiness from the perspective of Islamic law. The study employs a socio-legal approach with a qualitative methodology, utilizing interviews, observations, and document analysis. The findings reveal that the phenomenon is influenced by four primary factors: family trauma, exposure to negative content on social media, concerns regarding education and career development, and economic insecurity shaped by local socio-economic conditions. The findings further indicate that fear of marriage does not necessarily reflect a rejection of the institution of marriage; rather, it more frequently represents inadequate marital readiness. By integrating Marital Readiness Theory with the framework of maqāṣid al-sharī‘ah, this study proposes a reconstruction of marital readiness encompassing four principal dimensions: psychological, social, economic, and spiritual preparedness. These dimensions are oriented toward the realization of the objectives of protecting religion (ḥifẓ al-dīn), life (ḥifẓ al-nafs), intellect (ḥifẓ al-‘aql), lineage (ḥifẓ al-nasl), and property (ḥifẓ al-māl). This study affirms that strengthening marital readiness in a comprehensive manner constitutes a more contextual Islamic legal response to addressing the 'marriage is scary' phenomenon among Generation Z in the digital era.